Strategies to Improve the Quality of the Indonesian Air Force Military Police Investigators in Facing Crime Challenges in the Society 5.0 Era - Tamrin, Tamrin; Jamrudin, Hasrin; Bidul, Sayang; Ashar, Fitriyani (CV. Strata Persada Academia, 2024)
This study aims to formulate a strategy to improve the quality of Indonesian Air Force Military Police investigators in facing the challenges of crime in the Society 5.0 era. The Society 5.0 era is marked by rapid technological advances, especially in cyber and information technology fields, which have given birth to various new and increasingly sophisticated crime modes. Indonesian Air Force Military Police investigators must have adaptive and innovative competencies in dealing with the threat of crime in this era. This study uses a descriptive qualitative method with content analysis of secondary data from related literature and in-depth interviews with informants. The study results indicate that improving the quality of investigators through education and training programs that focus on cyber law, information technology, and digital investigation techniques is the primary strategy that needs to be implemented. In addition, adequate budget allocation and curriculum development are needed to respond to the development of crime in the Society 5.0 era. Cooperation with various parties is also essential to increase the exchange of information and the capacity of investigators. By implementing the right strategy, Indonesian Air Force Military Police investigators are expected to be able to face the challenges of crime in the Society 5.0 era professionally and with integrity.